2017
DOI: 10.1099/jmm.0.000467
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study of carbapenemase genes in clinical isolates of Enterobacteriaceae resistant to carbapenems and determining their clonal relationship using pulsed-field gel electrophoresis

Abstract: Our results could reflect some hospital multidrug-resistant strains in nosocomial infections. The widespread emergence of carbapenem-resistant isolates has caused increasing concern in recent years. Therefore, specific strategies should be designed and evaluated for the control of resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Epidemiological investigation such as PFGE is used for the bacteria isolates outbreak and also isolates transmission among patients, and within hospital wards. 23 In this study, PFGE analysis showed that K. pneumoniae was divided into 11 clusters and 3 singletons. The largest clusters had 4 similar isolates, and the other clusters had 2 or 3 identical isolates (Figure 1).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Epidemiological investigation such as PFGE is used for the bacteria isolates outbreak and also isolates transmission among patients, and within hospital wards. 23 In this study, PFGE analysis showed that K. pneumoniae was divided into 11 clusters and 3 singletons. The largest clusters had 4 similar isolates, and the other clusters had 2 or 3 identical isolates (Figure 1).…”
Section: Discussionmentioning
confidence: 67%
“…The rate of resistance to imipenem and meropenem in our strains is in line with other studies in Tehran, Egypt, and China. [23][24][25] Carbapenemase such as bla NDM is a plasmid-borne gene; 25 so, it may have readily been transmitted to other susceptible bacteria and make them resistant to carbapenemase, which might lead to failure in controlling spread of these bacteria in the hospital environment. This study investigated the prevalence of carbapenemase genes (bla NDM and bla OXA-48 were 45% and 10%, respectively); these genes were isolated from different wards, especially the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was used as a template for polymerase chain reaction (PCR) assay. PCR assays were carried out for detection of KPC, NDM, and OXA-48 genes using a set of specific primers as previously described (Table 1) (2,(18)(19)(20)(21). Standard strains for blaOXA-48, blaNDM, and blaKPC genes were provided by the Pasteur Institute of Iran.…”
Section: Molecular Detection Of Genes Encoding Carbapenemasesmentioning
confidence: 99%
“…Nosocomial infections, a major public healthcare problem, are more prevalent in developed countries because of the related mortality and socioeconomic costs (2). Enterobacteriaceae is one of the major causative agents of nosocomial infections (3,4).…”
Section: Introductionmentioning
confidence: 99%